Social justice and health – critical review - Vaughn, Laura (2010)
Abstract This critical review illustrates the structural barriers to equity of access to the NHS through the example of single parent families. An analysis of literature demonstrates that these structural barriers are classified as macro, meso and micro barriers and include the UK economy, government policy and the welfare system, and the education system on a macro level, right down to micro factors such as childcare and individual motivation. These barriers were found not just to have an impact on the single parent families ability to access NHS services but effect them in every aspect of daily life. It is suggested that government policy reform including the increasing of welfare entitlement would help improve the situation. It has been identified that an important detriment to health is the inequality in society so polices have been suggested as a means of bringing equality. Single parent families are an important group with regards to their accessing of the NHS due to their increasing number in society and high needs as consumers of NHS care. Nursing practice is made reference to throughout the dissertation with recommendations for practice including: non- discriminatory care, flexible enforcement of hospital rules and regulations relating to visiting times and accompanying children and using the political vote to elect a party committed to eradicating health inequalities and improving access to the NHS for societal groups such as single parent families.